New water-soluble chitin derivative with high antibacterial properties for potential application in active food coatings. (1st May 2021) - Kritchenkov, Andreii S.; Kletskov, Alexey V.; Egorov, Anton R.; Tskhovrebov, Alexander G.; Kurliuk, Aleh V.; Zhaliazniak, Natallia V.; Shakola, Tatsiana V.; Khrustalev, Victor N.
Highlights: Ultrasonic chitin polymer-analogous transformation is described for the first time. The transformation is regioselective and proceeds under Green Chemistry conditions. The synthesized chitin derivatives are water-soluble, non-toxic and have high antibacterial activity. A highlight on mode of antibacterial action of corresponding derivatives is given. The coating based on the chitin derivative improves the shelf life of Ricotta cheese. Abstract: The synthesis of new chitin derivatives through ultrasound-assisted treatment of the chitin with 1-azido-3-chloropropan-2-ol under Green Chemistry conditions is described. This is the first example of ultrasound-assisted polymer analogues transformation of chitin unaccompanied by noticeable backbone degradation or deacetylation. The obtained water-soluble azido chitin derivatives are characterized by high antibacterial activity, which is comparable with that of commercial antibiotics ampicillin and gentamicin. At the same time, they were demonstrated almost identical in vitro toxicity as unmodified chitin and chitosan. The antibacterial activity of the obtained polymers is mainly provided by azido moiety in their macromolecules. The conjugation of azido moiety to chitin backbone strongly diminishes the toxicity of the azido pharmacophore, but preserves its antibacterial properties. The most potent chitin derivative was used for the film coating of Ricotta cheese samples. This food coating proved to be efficient for the prolongation of shelf life of Ricotta cheese.